Peran Penting Bahasa dalam Komunikasi untuk Membangun Hubungan Pertemanan di Kampus - Audina Kania Ningrum; Muhammad Fauzi Nashrul Islam (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This article discusses the importance of the role of language in communication as a tool for building friendships on campus. Where language not only functions as a means of conveying information, but also functions as a bridge to understand culture, emotions, and personal identity. Interaction between students from different backgrounds on campus requires a thorough understanding of the proper use of spoken and written language. This research reveals how language facilitates social interaction, creates mutual trust, and strengthens bonds between friends. The method used for this research is a qualitative method using observation techniques and interviews with several students fr om various different backgrounds. The results of the observations and interviews conducted show how important language is to be a bridge of communication or as a means for students to interact with each other, besides that language is also a symbol of unity and unity of Indonesian society. In addition, this article also explores the challenges students face when communicating and provides recommendations for improving their communication skills. A thorough understanding of the role of language will help students develop more positive and productive friendships in a campus environment.